THE TWENTIETH CENTURY DEVELOPMENT OF DIFFERENT TYPES OF BACTERIAL, BIOLOGICAL AND CHEMICAL WEAPONS AND THE PRESENT CAPABILITIES OF NATO AND THE WARSAW PACT IN THIS RESPECT - Hudson, A.L.S. (Scientia Militaria - South African Journal of Military Studies, 2012)
Over the last twenty years increased attention has been focused on the military uses of Bacterial, Biological and Chemical agents (BBC weapons). This phenomenon can be attributed to a number of reasons. Firstly, BBC weapons are comparatively cheap and simple to produce, they are easy to use as conventional weapons and their effects are short-lived. The mutual deterrence effect of nuclear weapons, furthermore, has necessitated the exploration of other fields of warfare of which - BBC warfare is a field. Another reason for this interest is the employment, on a limited scale, of such weapons in certain conflicts over this period.